Risks of low birth weight, small-for-gestational age and preterm births following the economic collapse in Iceland 2008 - Védís Helga Eiríksdóttir 1977- (2011)
Infants born small or preterm have increased rates of mortality and morbidity throughout childhood and into adulthood. Stressful events have been suggested as potential contributors to preterm birth (PB) and low birth weight (LBW). We aimed to study the effect of the 2008 national economic collapse in Iceland on the risk of these adverse birth outcomes. The study population constituted all Icelandic women giving birth to live-born singletons from January 1st 2006 to December 31st 2009. LBW infants were defined as those weighing <2500g at birth, PB infants defined as those born before 37 weeks of gestation and small-for-gestational age (SGA) defined as infants with birth weight less than two standard deviation below the mean on a fetal growth curve. Exposure to the collapse of the Icelandic banking system was modeled with calendar time. We used logistic regression to estimate odds ratios [OR] and the corresponding 95 percent confidence intervals [95%CI] of these adverse birth outcomes by exposure to calendar time of the economic crisis, i.e. after October 6th 2008. Compared to the preceding period, we observed a short-term increase in LBW deliveries following the economic collapse (aOR=1.24, 95% CI [1.02, 1.52]), particularly among children born to women younger than 25 years (aOR=1.85, 95% CI [1.25, 2.72]) and mothers not working (aOR=1.59, 95% CI [1.10, 2.31]). Similarly, we found a tendency towards higher incidence of SGA births (aOR=1.14, 95% CI [0.86, 1.51]), particularly among children born to women younger than 25 years (aOR=1.85, 95% CI [1.08, 3.19]) and to women not working (aOR=1.84, 95% CI [1.09, 3.10]). We found no change in the risk of PB. The results suggest a short term increase in incidence of low birth weight following the dramatic collapse of the Icelandic national economy. The increase in LBW seemed driven by reduced fetal growth rate rather than shorter gestation. Börn sem fædd eru of létt eða fyrir tímann eru í aukinni áhættu varðandi nýburadauða auk þess sem þau eiga oft við ...